L'enseignant(e) de mathématiques, un modèle de rôle social bénéfique à l'orientation asexuée des élèves ? - Armel Valdin Teague Tsopgny (Nantes Université, 2021)
While research highlight the positive effect of the female role model in girls' studies in mathematics, gender disparities are still observed in this domain, in the presence female teacher in classrooms. Based on the stereotype threat theory and the social cognitive framework, we study from mathematics teachers, the effect of sex role model on stereotype endorsement, self-efficacy and the choice of students on the math domain, according to sex. 64 girls and 79 boys in the science classes at secondary high school took part in this study. The results reveal the absence of positive effect on girls from the female teacher on the measures indicated, in comparison to the male teacher. These results are discussed in the light of the studies on mathematics teachers' practices according to sex of student.